VALUASI NILAI SAHAM PERUSAHAAN NON-TBK DALAM PELAKSANAAN IMPAIRMENT GOODWILL - Izath Rytami; Primadonna Ratna Mutumanikam (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This study aims to analyze the causes of the emergence of goodwill in the acquisition of company shares, analyze how the stages in performing goodwill impairment on the parent company, and analyze how to evaluate the shares of non-listed companies and their effect on goodwill impairment. This study focuses on a case study on PT Tebu as the object of acquisition by testing goodwill using the income approach and the Discounted Cashflow method. Based on the case study, it is concluded that goodwill in an acquisition arises due to the difference between the excess of fair value and book value over the acquisition price of shares, and it is also known that the stages in implementing impairment goodwill are by comparing Goodwill per Book with Goodwill based on fair value (test results) currently on the books of the Parent Company.